Pengelolaan Logistik dan Pengadaan Barang Di TMG Hotel Jakarta - Pambudi, Anjar; Hartati, Leni; Abriandi, Abriandi (Universitas Batanghari Jambi, 2026)
This study aims to examine the management of logistics and procurement processes at TMG Hotel Tebet with a focus on procedures, receiving, and inventory management as a basis for preparing internship reports. The results of this study are Based on the experience of students during their internship at TMG Hotel Jakarta, logistics and procurement management in general have run well and according to procedures, but there are still several obstacles that need attention, such as late arrival of goods not according to the purchase order schedule, discrepancies in the number, type, or specifications of goods with the PO, inaccuracies in inventory recording that cause stock differences, less than optimal communication between departments with the logistics or purchasing section, and limited storage space that causes goods management to be less efficient, especially when the volume of goods increases.